A COMPLEX RELATIONSHIP BETWEEN CHINESE IMMIGRANT MOTHER AND AMERICANISED DAUGHTER IN "THE BONESETTER'S DAUGHTER" BY AMY TAN - Erejepbaeva Shakhnoza; Dilnoza Ruzmatova (Journals Park Publishing, 2023)
The aim of this study is to discuss the relationship between mothers and daughters in "The Bonesetter's Daughter" by Amy Tan. Three female characters from separate generations—Precious Auntie, LuLing, and Ruth—are crucial to the plot and are remembered in fragments. The novel's plot is divided into multiple levels of narration, with the opening section serving as the book's basic structural unit. The author, uses a variety of stories featuring several characters, especially those focused on the mother-daughter relationship, rather than concentrating on just one to convey ethnic anxieties and identity. Forgetfulness.
Keywords: Amy Tan, Relationship, mother and daughter. The bonesetter's daughter. Culture. Traditions. Misunderstanding. Truth.